Perception of the fisheries resources and life aspirations of young people in the Visayan sea - Ferrer, Alice Joan G. (Danyag : Journal of Humanities and Social Sciences, 2007)
The respondents of the study were 384 young people aged 16 to 21. They were proportionately drawn from fishing and non-fishing households in 16 randomly selected coastal/island barangays in four randomly selected municipalities/city in the provinces surrounding the Visayan Sea: Concepcion (Iloilo), Sagay City (Negros Occidental), Medellin (Cebu), and Milagros (Masbate). Compared with the 259 non-fisher-respondents, most of the 125 fisher-respondents were generally male natives from fishing/fishing-related households whose houses were near the sea and far from the basic infrastructure facilities and town center and living in barangays with higher proportion of fishers to population. When classified by type of respondents, there is no pronounced difference in the number who perceived that fishery resources are depleted. They identified the following problems and issues in fishing: illegal fishing; use of fine-meshed nets; encroachment of commercial fishers into municipal waters and pollution. Fewer of the fisher-respondents compared to non-fisher-respondents were hopeful of a better future. The majority of them plan to leave fishing. In general, they did not differ with the non-fisher-respondents in terms of life goals and aspirations.